PENGARUH KOMPENSASI, MOTIVASI, DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA SHOPEE EXPRESS KABUPATEN BANDUNG - Taufiq, Mukholli; Recky, Recky; Sari, Yane Puspito (Ikatan Sarjana Ekonomi Indonesia Cabang Pekanbaru, 2024)
This study aims to analyze the influence of compensation, motivation, and job satisfaction on employee performance at Shopee Express in Bandung Regency. Using a quantitative method grounded in positivist philosophy, data were collected from the entire population of operational staff and daily-wage earners, totaling 35 individuals, through a census approach. The analysis revealed that job satisfaction has the most significant and positive impact on performance, indicating that increased job satisfaction directly enhances employee performance. Additionally, motivation also significantly contributes to improving employee performance. In contrast, compensation was found to have no significant effect on performance, as evidenced by a statistically insignificant negative coefficient. These findings highlight the crucial role of job satisfaction and motivation as primary factors in enhancing performance while emphasizing the need for further evaluation of compensation strategies. This study provides strategic insights for Shopee Express management to prioritize improving job satisfaction and motivation to support sustainable productivity. Keywords: Compensation, Motivation, Job Satisfaction, Employee Performance